2002
DOI: 10.1021/jp013210m
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Study of CHx Chemisorption and Transition States for C−H Activation on the Ru(112̄0) Surface

Abstract: The thermodynamics of methane decomposition on the ruthenium (1120) surface has been investigated with ab initio periodic calculations. All surface intermediates are more stable than the gas-phase methane even if the last step of the decomposition path: CH f C + H, is highly endothermic. Among all of the surface species, CH 2 appears to be the most stable. All of the surface species (CH x , x ) 3-1 and H) adsorb on bridge-up sites, while atomic C prefers top-down sites. The transition states of the elementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 26 publications
4
52
1
Order By: Relevance
“…Our activation energies for the reactions R.1, R.3, R.6, and R.10dehydrogenation reactions in methaneagree well with previous first-principles results 28 (Table 1).…”
Section: ■ Resultssupporting
confidence: 90%
“…Our activation energies for the reactions R.1, R.3, R.6, and R.10dehydrogenation reactions in methaneagree well with previous first-principles results 28 (Table 1).…”
Section: ■ Resultssupporting
confidence: 90%
“…They concluded that ethylene should be formed through dehydrogenation of ethane and not by coupling of methane. Ciobica et al 19 calculated that on Ru (1120), the most stable species is CH 2 * and that the intermediates CH x (1 < x < 3) are more stable when adsorbed on bridged sites, while C species are preferentially adsorbed on top sites.…”
Section: Discussionmentioning
confidence: 99%
“…The same effect has been found for a number of other molecules. [35][36][37][38][39][40][41] Such effects are clearly important in determining the activity of a catalyst. For reactions where steps have a high reactivity, the density of such sites on the supported nanoparticle catalysts is a crucial parameter.…”
Section: The Geometrical and Electronic Factor In Catalysismentioning
confidence: 99%